2017
DOI: 10.1093/jpepsy/jsx122
|View full text |Cite
|
Sign up to set email alerts
|

Featured Article: The ABCDs of Pain Management: A Double-Blind Randomized Controlled Trial Examining the Impact of a Brief Educational Video on Infants’ and Toddlers’ Pain Scores and Parent Soothing Behavior

Abstract: The ABCD pain management strategy delivered via video was an effective way to reduce toddler pain after vaccination and increase parental use of rocking and physical comforting. The treatment effect was not demonstrated with infants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
37
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(38 citation statements)
references
References 15 publications
(18 reference statements)
1
37
0
Order By: Relevance
“…The recommended approach for postsurgical management is multidisciplinary using various analgesic options including nonpharmacological interventions and local regional techniques combined with medications having different mechanisms of action 73,74. Nonpharmacological interventions may, for example, include distraction/comforting,8284 whereas the application of topical liposomal lidocaine85 and the transversus abdominis plane block86 are examples of local regional techniques with demonstrated efficacy.…”
Section: Pain In Childrenmentioning
confidence: 99%
“…The recommended approach for postsurgical management is multidisciplinary using various analgesic options including nonpharmacological interventions and local regional techniques combined with medications having different mechanisms of action 73,74. Nonpharmacological interventions may, for example, include distraction/comforting,8284 whereas the application of topical liposomal lidocaine85 and the transversus abdominis plane block86 are examples of local regional techniques with demonstrated efficacy.…”
Section: Pain In Childrenmentioning
confidence: 99%
“…The current study conducts secondary post hoc analyses of a double-blind RCT evaluating the efficacy of a parent psychoeducational video for young child pain management (Treatment Video vs. Placebo Video), at two ages (Infant: 6 months; Toddler: 18 months), on young child pain and parent soothing behaviors immediately following, and in the minutes post-vaccination (Pillai Riddell et al, 2017). The original RCT found that the treatment video was associated with lower pain scores in toddlers (1-and 2-min post-needle) but not infants.…”
Section: Current Studymentioning
confidence: 99%
“…This article presents a post hoc analysis contextualizing data from the original double-blind randomized controlled study stratified by age (infants and toddlers; Pillai Riddell et al, 2017). The initial RCT was multisite (two separate clinics), with balanced randomization (1:1) and parallel groups.…”
Section: Trial Designmentioning
confidence: 99%
See 2 more Smart Citations